2011
DOI: 10.1016/j.applanim.2011.06.009
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of three types of analgesic drugs in reducing pain in the rainbow trout, Oncorhynchus mykiss

Abstract: Recent research has shown the possibility of pain perception in fish; therefore, the use of analgesia or "painkillers" should be considered for invasive procedures. However, there is relatively little information on the effectiveness of analgesic drugs nor on the appropriate dose for fish. This study assessed the efficacy of three types of drug: an opioid, buprenorphine, a non-steroidal anti-inflammatory drug (NSAID), carprofen and a local anaesthetic, lidocaine. Each drug was tested at three doses on rainbow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 41 publications
5
69
1
Order By: Relevance
“…Thus, it seems prudent to explore the analgesic efficacy of aspirin in 5 dpf zebrafish. However, despite all this evidence, research on the use of NSAIDs as analgesics in fish is very limited (Davis et al, 2006;Harms et al, 2005;Mettam et al, 2011). Although the analgesic effects of aspirin have been investigated in other animals (Jablonski and Howden, 2002;Shyu and Lin, 1985), we found no studies in larval or adult fish.…”
Section: Experiments 1: Impact Of Noxious Chemicals On Larval Behaviourcontrasting
confidence: 52%
See 1 more Smart Citation
“…Thus, it seems prudent to explore the analgesic efficacy of aspirin in 5 dpf zebrafish. However, despite all this evidence, research on the use of NSAIDs as analgesics in fish is very limited (Davis et al, 2006;Harms et al, 2005;Mettam et al, 2011). Although the analgesic effects of aspirin have been investigated in other animals (Jablonski and Howden, 2002;Shyu and Lin, 1985), we found no studies in larval or adult fish.…”
Section: Experiments 1: Impact Of Noxious Chemicals On Larval Behaviourcontrasting
confidence: 52%
“…Finding an alternative to the use of adult fish in these studies is a priority as is finding a rapid means of testing the efficacy of analgesics if we are to adopt an ethical 3Rs (Replacement, Reduction and Refinement) approach to research (Russell and Burch, 1959). However, a very limited number of studies have investigated the effects of analgesics in fish and most of these have explored intramuscular injection, which is impractical for small species such as zebrafish (Harms et al, 2005;Mettam et al, 2011;Sneddon, 2003). Therefore, a range of doses of these analgesic agents administered via immersion (dissolved in tank water) need to be investigated to determine their efficacy as a high-throughput means of testing drugs in a large number of unprotected 5 dpf zebrafish.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies have examined the influence of nociceptive stressors on these axes. The injection of acetic acid in the lips of rainbow trout did not influence cortisol levels (Mettam et al, 2011), but increased the opercular beat rate indicating an increase in the ventilation rate during the first hours following the administration (Sneddon, 2003;Mettam et al, 2011). This increase was reversed when trouts were treated with morphine, indicating the nociceptive implication of the changes (Sneddon, 2003).…”
Section: Physiological Indicatorsmentioning
confidence: 82%
“…One or more of these behavioural changes occurred in the three studied species: zebrafish, trout and carp (Reilly et al, 2008). Experiments in rainbow trout showed that morphine or local anaesthesia with lidocaine reduced these behavioural changes in acid-treated animals (Sneddon, 2003;Mettam et al, 2011), indicating that they were dependant on pain.…”
Section: Postural and Behavioural Indicatorsmentioning
confidence: 99%
“…(2009), which tested morphine and had demonstrated pain perception in these fishes. [29,30] Studies have demonstrated, after injury in medial and lateral pallium, avoiding behavioral learning in goldfish and showing involvement by these telencephalic structures in this process. [31,32] Asphyxia on ice or evisceration without any anesthesia are common examples of killing methods used in fish farming.…”
Section: Pain Perception and Fearmentioning
confidence: 99%